Earth keeping and character: exploring a Christian ecological virtue ethic. - Steven Bouma-Prediger (Grand Rapids Baker Academic, 2020)
Addressing a topic of growing and vital concern, this book asks us to reconsider how we think about the natural world and our place in it. Steven Bouma-Prediger brings ecotheology into conversation with the emerging field of environmental virtue ethics, exploring the character traits and virtues required for Christians to be responsible keepers of the earth and to flourish in the challenging decades to come.
Keywords: Ecological Ethics, Self-Control and Wisdom, Virtue Ethics, Justice and Love